2000
DOI: 10.1016/s0002-9440(10)64526-9
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Inhibitor Tyrphostin AG126 Reduces the Development of Acute and Chronic Inflammation

Abstract: Protein tyrosine kinases help to regulate the expression of many genes that play important roles in inflammation. Here we investigate the effects of the tyrosine kinase inhibitor tyrphostin AG126 in two animal models of acute and chronic inflammation, carrageenan-induced pleurisy and collagen-induced arthritis. We report here that tyrphostin AG126 (given at 1, 3, or 10 mg/kg i.p. in the pleurisy model or 5 mg/kg i.p. every 48 hours in the arthritis model) exerts potent anti-inflammatory effects in animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Because the activation of several PLA 2 isoforms can be influenced by phosphorylation (19), it is conceivable that AG-126 may inhibit a kinase that couples K ϩ efflux to iPLA 2 activation. The molecular target of AG-126 is likely to be important for the inflammatory role of the P2X 7 R, because treating mice with AG-126 is able to prevent anti-collagen-induced arthritis, a disease model in which the P2X 7 R has also been implicated (8,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the activation of several PLA 2 isoforms can be influenced by phosphorylation (19), it is conceivable that AG-126 may inhibit a kinase that couples K ϩ efflux to iPLA 2 activation. The molecular target of AG-126 is likely to be important for the inflammatory role of the P2X 7 R, because treating mice with AG-126 is able to prevent anti-collagen-induced arthritis, a disease model in which the P2X 7 R has also been implicated (8,20).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate how brief P2X 7 R activation of intact macrophages induces accelerated caspase-1 and IL-1␤ processing in cell-free lysates, we tested whether any common signaling components might be required for the basal activation of caspase-1 processing by hypotonic lysis and the acceleration of caspase-1 processing after P2X 7 R stimulation. Previous studies have reported that AG-126, a tyrphostin family tyrosine kinase inhibitor, can block inflammatory responses in vivo as well as ATP-mediated caspase-1 activation and secretion of IL-1␤ and IL-18 from human monocytes (8,25). The specific target of AG-126 is unknown.…”
Section: Stimulation Of K ϩ Loss From Intact Cells Is Necessary For Imentioning
confidence: 99%
“…We also used kringles 1-5, a proteolytic cleavage fragment of endogenous plasminogen protein, as a therapy targeting angiogenesis in CIA (20). In animal models of arthritis in mice and rats, as well as in an acute inflammatory recruitment air pouch model, blocking of angiogenesis by targeting the tyrosine kinase activity of VEGFR has been demonstrated (46); in addition, tyrosine kinase inhibition by other synthetic compounds in autoimmune arthritis and chronic inflammatory conditions has been described (47). Engagement of HER receptors has been known to increase the release of the proangiogenic factor VEGF in cancers (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Before injection, CII was emulsified with an equal volume of CFA. CIA was induced as described previously (Szabó et al, 1998;Cuzzocrea et al, 2000b). On day 1, mice were injected intradermally at the base of the tail with 100 l of the emulsion (containing 100 g of CII).…”
Section: Methodsmentioning
confidence: 99%